2014
DOI: 10.1007/s12282-014-0535-1
|View full text |Cite
|
Sign up to set email alerts
|

The role of sentinel node biopsy in male breast cancer

Abstract: SLNB is successful and accurate in male breast cancer patients too. Although compared to women a larger proportion of men have positive nodes, for men with negative nodes, ALND-related morbidity may be reduced by SLNB. We recommend SLNB in male patients with breast cancer and clinically negative axilla.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…Our study showed men were less like to undergo sentinel node biopsy/sampling than women. There was no difference in rates of axillary dissection for invasive disease, as reflected by equivalent rates of >94% of males and females meeting the third KPI 21,22 . A greater proportion of males had stage II or III disease at diagnosis, and this may explain the higher likelihood of males undergoing level 1–3 axillary clearance, than females.…”
Section: Discussionmentioning
confidence: 94%
“…Our study showed men were less like to undergo sentinel node biopsy/sampling than women. There was no difference in rates of axillary dissection for invasive disease, as reflected by equivalent rates of >94% of males and females meeting the third KPI 21,22 . A greater proportion of males had stage II or III disease at diagnosis, and this may explain the higher likelihood of males undergoing level 1–3 axillary clearance, than females.…”
Section: Discussionmentioning
confidence: 94%
“…There have been several series reporting ≥ 30 sentinel node biopsies for MBC, all from the USA which have been summarised in Table 2 [ 41 46 ]. The lowest identification rate (90%) occurred in the series in which not all cases received both isosulfan blue and technetium-99m [ 35 ].…”
Section: Sentinel Node Biopsymentioning
confidence: 99%
“…Successful SLN identification rates in the male breast cancer population have been reported to be 93 to 100 per cent in the literature, as shown in the Table 1. [6][7][8][9][10][11][12][13][14][15] Furthermore, a study by Rusby 14 et al evaluated the overall accuracy of SLN biopsy in male breast cancer and found that the identification rate was 96 per cent in 110 patients.…”
Section: Discussionmentioning
confidence: 99%